Training On Children's Independence In Learning In Elementary Schools In Mataram City - Zulfakar (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Independent learning is a key competency in developing the character of 21st-century students. A child's ability to learn independently not only reflects mental and emotional readiness but is also a crucial indicator of success in basic education. Through this community service activity, the implementing team strives to foster and strengthen independent learning in elementary school students in Mataram City through a structured and participatory training program. The activity took place on March 14–15, 2025, at one of the partner elementary schools, with direct involvement of students, teachers, and parents. The methods used included an active learning approach, independent learning simulations, the use of simple digital learning media, and discussion sessions between teachers and parents to foster a shared understanding of the importance of supporting, but not dominating, their children's learning process. During the activity, students were presented with various learning challenges that guided them to manage their time, determine strategies for completing assignments, and self-evaluate their learning outcomes. The results of the activity showed improvements in several indicators of independent learning, such as increased student initiative in completing assignments without direct guidance, the ability to organize simple study schedules, and the courage to express opinions. Teachers began implementing learning strategies that provide space for student exploration, while parents better understood how to support their children's learning without over-interference. Overall, this community service activity had a positive impact on collective awareness of the importance of developing a culture of independent learning from an early age. This program is expected to serve as an initial model for developing contextual and sustainable character education in elementary schools.